Analisis Perencanaan Pembangunan Daerah dalam Pemanfaatan Dana Kelurahan di Kota Bima - Rahman, Fazhur (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2022)
The background of this research is the policy of allocation of urban village funds from the central government at the end of 2018.This is carried out to stimulate local governments, including Bima City to support sub-district village development through local government budget (APBD) allocation of 5%. This research is qualitative research. The results of this study is seen from the lack of authority (decentralization) given to the chief of the administrative village with limited space and role, the community is less empowered and involved in the planning and implementation of village funds. Meanwhile, the factors affecting the management of the village funds in Bima City are the dominance of regional agencies; human resources; rapid changes in the organizational structure; the inaccuracy of understanding the planning of village funds; Lack of transparency and dissemination of information.